Penerapan Prinsip – Prinsip Ekonomi Syariah Dalam Pengembangan Pasar Modal - Alif Zainul Hisyam; Fauzatul Laily Nisa (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
This research explores the application of sharia economic principles in the capital market and its impact on market stability and efficiency. The principles of sharia, including the prohibitions on usury, gharar, and maisir, provide a unique ethical and legal framework. Financial instruments such as sukuk, Islamic mutual funds, and Islamic stock indices offer alternatives for Muslim investors. This study found that these instruments are not only compliant with sharia but also able to attract the interest of investors who want to avoid transactions prohibited in Islam. However, challenges such as the need for strict regulation and increased awareness still need to be overcome. Nevertheless, the Islamic capital market has great potential to support a more inclusive and stable financial system. This research uses qualitative descriptive analysis with literature study methods and content analysis to identify and analyze sharia financial instruments used in the capital market, including sukuk, sharia mutual funds, and sharia stock indices. Through this analysis, it was found that Islamic financial instruments not only comply with sharia requirements but also offer an attractive alternative for Muslim investors who wish to avoid transactions considered haram in Islam.